2011
DOI: 10.1007/s10439-011-0467-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Noninvasive Measurement of Systolic and Diastolic Blood Pressure by One Mathematical Model with the Same Model Parameters and Two Separate Pulse Wave Velocities

Abstract: There is keen interest in continuous and noninvasive blood pressure (BP) measurement. However, many technologies have a shortcoming of complex mechanical structure. In our study, two arterial pulses are acquired by photoplethysmography (PPG) at ear and toe in order to explore a new method of measuring BP by pulse wave velocity (PWV). We previously validated and reported a BP-PWV mathematical model with measurements from humans with no evidence of cardiovascular disease, but were only able to determine PWV rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…These peaks are distorted by reflection of pressure waves from the terminal arteries. Chen et al proposed a novel method based on experimental data to use the mean of PTT fp (time delay between falling edge of central PPG and peak of peripheral PPG) and PTT rp (time delay between rising edge of reflecting central PPG and peak of peripheral PPG) to obtain PTT for SBP (Figure 3c) [63]. Other studies have indicated that posture, ambient temperature, and relaxation affect PPG, raising a question on the development of an accurate PTT device [64].…”
Section: Pulse Transit Time (Ptt)mentioning
confidence: 99%
“…These peaks are distorted by reflection of pressure waves from the terminal arteries. Chen et al proposed a novel method based on experimental data to use the mean of PTT fp (time delay between falling edge of central PPG and peak of peripheral PPG) and PTT rp (time delay between rising edge of reflecting central PPG and peak of peripheral PPG) to obtain PTT for SBP (Figure 3c) [63]. Other studies have indicated that posture, ambient temperature, and relaxation affect PPG, raising a question on the development of an accurate PTT device [64].…”
Section: Pulse Transit Time (Ptt)mentioning
confidence: 99%
“…There are two typical methods to measure PTT. The first [14] is to calculate the delay between Electrocardiogram (ECG) and PPG, and the second method [15] is to measure the delay of different PPGs acquired from different parts of the body. To improve the accuracy of the evaluation of BP, a new feature vector extraction algorithm was proposed by Li et al in [16].…”
Section: Introductionmentioning
confidence: 99%
“…where f(PTT) could be PTT [39,[49][50][51][52][53][54][55][56][57] or its variants, such as 1/PTT [58,59], 1/PTT 2 [60,61], ln(PTT) [40,61], and e k*PTT [62] [63]. Rather than only PTT, extra parameters related to cardiovascular activity can be introduced:…”
Section: Ptt-bp Modelingmentioning
confidence: 99%